Demographic Predictors of Mothers' Willingness to Vaccinate Young Children Against COVID-19, Get Tested and Isolate: A Cross-Sectional Survey Before and During the Greater Sydney Lockdown 2021, Australia - Li Ming Wen; Li Ming Wen; Li Ming Wen; Li Ming Wen; Li Ming Wen; Huilan Xu; Huilan Xu; Chris Rissel; Erin Kerr; Limin Buchanan; Limin Buchanan; Limin Buchanan; et al. (Frontiers in Public Health, 2022)
Background and ObjectivesHaving a COVID-19 vaccination, getting tested, and self-isolating if symptomatic are some of the most important mitigation strategies for preventing the spread of COVID-19. This study aimed to investigate whether demographic factors are associated with mothers' willingness to vaccinate their 4-year-old children against COVID-19 if a suitable vaccine becomes available or to get tested and self-isolate if they themselves have COVID-19 symptoms and whether the willingness could be influenced by the Greater Sydney lockdown 2021.MethodsA cross-sectional telephone survey was conducted between 24th February and 26th October 2021. Questions from the NSW Adult Population Health Survey and from previously published studies were used to assess family demographics, mothers' willingness to vaccinate their young children, and willingness to get tested and self-isolate if symptomatic. The survey involved 604 mothers of children aged 4 years who participated in an existing trial in Sydney, Australia.ResultsMothers were more willing to vaccinate their children when the child's father had a tertiary education or higher, with an adjusted odds ratio (AOR) of 2.60 (95% CI 1.67–4.04). Mothers who were older than 30 years or who completed the survey during the lockdown were more willing to get tested if symptomatic, with AOR 2.50 (95% CI 1.17–5.36) and AOR 3.36 (95% CI 1.41–8.02), respectively. Mothers who were married or had de-facto partners were more willing to self-isolate if symptomatic [AOR 17.15 (95% CI 3.56–82.65)].ConclusionFathers' educational level, mothers' age, and marital status were associated with mothers' willingness to vaccinate their young children if a suitable vaccine were available, to get tested, and self-isolate if symptomatic respectively. The promotion of mitigation strategies for tackling the COVID-19 pandemic needs to take into account specific family demographics.